Evaluation of the energy saving opportunities for palm oil refining process: Sahabat Oil Products (SOP) in Lahad Datu, Malaysia - Lidu, S.R. (Springer Verlag, 2016)
Palm Oil industry is one of the major contributors to Malaysiaâs economic activity. Accounting for 39Â of the world palm oil production and 44Â of world exports, Malaysia holds an important niche in fulfiling the growing global needs for oils and fats sustainably. This industry has high potential for further improvements especially in terms of energy saving as a major contributor to cost and emission reduction. An analysis of the refining process of palm oil in Sahabat Oil Products, Lahad Datu has been performed and presented in this paper for scoping potential energy and cost savings using heat integration. A first stage optimisation of the minimum temperature difference, âTmin, of a heat exchanger network (HEN) has been performed. The goal has been to evaluate the maximal possible heat recovery as well as the appropriate placement of utilities. The HEN design is presented in both grid diagram and shifted retrofit thermodynamic grid diagram (SRTGD). SRTGD representation has been illustrated in this paper as a useful tool for guiding eventual future retrofit. The capital-energy trade-off of the heat recovery targets indicates optimum âTmin of 12.3Â Â°C. The hot and cold utility targets at âTminÂ =Â 12.3Â Â°C are 1419 and 1649Â kW, indicating potential saving of 3.5 and 3.1Â as compared to the existing utility consumption and emissions. Future work could proceed further to seek potentially viable retrofit of the existing heat recovery network. Â© 2016, Springer-Verlag Berlin Heidelberg.